NMDARs Drive the Expression of Neuropsychiatric Disorder Risk Genes Within GABAergic Interneuron Subtypes in the Juvenile Brain - Mahadevan, Vivek; Mitra, Apratim; Zhang, Yajun; Yuan, Xiaoqing; Peltekian, Areg; Chittajallu, Ramesh; Esnault, Caroline; Maric, Dragan; Rhodes, Christopher; Pelkey, Kenneth A.; Dale, Ryan; Petros, Timothy J.; et al. (Frontiers in Molecular Neuroscience, 2021)
Medial ganglionic eminence (MGE)-derived parvalbumin (PV)+, somatostatin (SST)+ and Neurogliaform (NGFC)-type cortical and hippocampal interneurons, have distinct molecular, anatomical, and physiological properties. However, the molecular mechanisms regulating their maturation remain poorly understood. Here, via single-cell transcriptomics, we show that the obligate NMDA-type glutamate receptor (NMDAR) subunit gene Grin1 mediates transcriptional regulation of gene expression in specific subtypes of MGE-derived interneurons, leading to altered subtype abundances. Notably, MGE-specific early-developmental Grin1 loss result in a broad downregulation of diverse transcriptional, synaptogenic and membrane excitability regulatory programs in the juvenile brain. These widespread gene expression abnormalities mirror aberrations that are typically associated with neurodevelopmental disorders. Our study hence provides a road map for the systematic examination of NMDAR signaling in interneuron subtypes, revealing potential MGE-specific genetic targets that could instruct future therapies of psychiatric disorders.